(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Women plays a critical role in maintaining health and overall wellbeing of her communities. Thebasic nutrition knowledge of women plays crucial role in maintaining her health as well as health of herfamily and society. Aim the aim of the study is to assess the knowledge regarding Basic Nutrition ofyoung adult women of aged 19-23 years of low socioeconomic group of Indore city of Madhya Pradesh.Methodology through purposive random sampling method, 120 women of slums of Indore have beenselected with their consent. Data collected by means of self-designed questionnaire and interviewmethod. Result obtained information showed the poor knowledge regarding basic nutrition of therespondents. Conclusion Nutrition Education program should be planned for the women of studiedgroup.